(untitled) (Damascus University Journal of arts and humanities sciences, 2021)
The region was subjected to serious political developments in the last centuries of the second millennium BC, and was made a single goal for these invading forces despite the multiplicity of kingdoms and empires there. Therefore, it is necessary to study the political developments in the Aegean Sea region and in Greece, and then to examine the political developments in the Anatolia and North Syrian regions in the early 14th century BC, as well as the political developments on the land of the Levant, especially between the Egyptians and the Hittites who were the masters of the entire region. In this research, reliance was mainly of the texts as sources of information for that period, particularly on the texts discovered in the Kingdom of Ugarit, the texts of the Amarna hill, and also the Egyptian texts, in order to study all the key points and even. The paper focuses on what happened to the region, during at least two centuries, and on the invasion that was not sudden and not for a short period of time as researchers have concluded it.